Mutational analysis of renal angiomyolipoma associated with tuberous sclerosis complex and the outcome of short-term everolimus therapy - Ni, Jianxin; Yan, Fengqi; Qin, Weijun; Yu, Lei; Zhang, Geng; Liu, Fei; Yang, Xiaojian; Yang, Bo; Hao, Chunlin; Wang, Teng; Liu, Pengfei; Yuan, Jianlin; et al. (Scientific reports, 2019)
To identify clinical characteristics and mutation spectra in Chinese patients with renal angiomyolipoma (AML) associated with the tuberous sclerosis complex (TSC, TSC-AML), examined the efficacy and safety of short-term everolimus therapy (12 weeks). We analyzed the frequency distribution of each TSC-related clinical feature and investigated gene mutations by genetic testing. Some subjects received everolimus for 12 weeks at a dose of 10 mg/day, and the efficacy and safety of short-term everolimus therapy were examined. Finally, 82 TSC-AML patients were enrolled for analysis in this study. Of the 47 patients who underwent genetic testing, 22 patients (46.81%) had at least one detectable mutation in the TSC1 or TSC2 gene: 7 were TSC1 gene mutations, 13 were TSC2 gene mutations, and 2 were found in both TSC1 and TSC2 . Everolimus treatment had a statistically significant effect on the renal AML volume reduction during follow-up ( P < 0.05), and the mean reduction rate of volume for all cases was 56.47 ± 23.32% over 12 weeks. However, 7 patients (7/25; 28.00%) experienced an increase in renal AML tumor volume within 12 weeks after discontinuation of the everolimus treatment. Although most patients (27/30, 90.00%) experienced some adverse events during the treatment period, all such events were mild, and no patients discontinued or needed dose reduction because of adverse events. Overall, in this study, the mutation rate of TSC-AML patients is much lower than other reports. Short-term everolimus treatment for TSC-AML is effective and safe, but the stability is much lower than long-term therapy.